1972
DOI: 10.1002/jsfa.2740230413
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional effects of including different levels and sources of protein in milk replacers for calves

Abstract: Two digestibility and nitrogen balance experiments were carried out with groups of young calves given high-fat milk replacers reconstituted with water and fed in liquid form. In the first experiment six different milk replacers with crude protein contents ranging from 12.7 up to 27.6% in the dry matter were compared, the differences in protein content being brought about by adjustments to the level of separated milk protein used in the replacers. The apparent digestibility of organic matter was very high on al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…Despite the linearly decreasing tendency, the differences in N retention were not significant. The results of this investigation are similar to those reported by Huber and Slide (1967), Raven (1972) and Opstvedt et al (1977). In all the investigated treatments, N balance was positive and N retention decreased with higher level of fish protein.…”
Section: Resultssupporting
confidence: 93%
“…Despite the linearly decreasing tendency, the differences in N retention were not significant. The results of this investigation are similar to those reported by Huber and Slide (1967), Raven (1972) and Opstvedt et al (1977). In all the investigated treatments, N balance was positive and N retention decreased with higher level of fish protein.…”
Section: Resultssupporting
confidence: 93%
“…These figures are in line with the digestibility found for the protein in other types of fish protein concentrates (Hellcmond, 1967;Huber & Slade, 1968;Sleiman & Huber, 1971;Gorrill et al, 1975;Raven, 1972;Sniits et al, 1974), and somewhat higher than those found for milk protein substitutes of vegetable, animal and single cell origin (Paruelle et al, 1973;Raven, 1972). The ability of the calf to digest protein of non-milk origin, therefore, improves with age.…”
Section: )supporting
confidence: 76%
“…In a separately conducted digestibility test (unpublished data) the apparent digestibility of the protein in Norsamin" was 73% when fed as the sole source of protein to calves between 1 and 4 weeks of age. Since the total protein content was different in milk replacers without and with Norsaniins in the present study, the apparent digestibility of the protein in Norsaniin" cannot be calculated directly by difference (Raven, 1972). However, assuming a n apparent digestibility of 93:/0 for the milk protein revealed that the protein in Norsaniin" was digested to about 80% for the younger calves (Expts.…”
Section: Nutrielit D(gestibility Atitljeetliiig Cnlirementioning
confidence: 81%
“…Applying these restrictions allowed data from 16 published papers to be used. Of these, 6 studied calves were fed milk or milk protein-based milk replacer (milk-fed group) with 37 different dietary treatments, with animals ranging from 30 to 81 kg of BW (Blaxter and Wood, 1951b;Brisson et al, 1957;Roy et al, 1970;Raven, 1972;Donnelly and Hutton, 1976;Blome et al, 2003). For animals in the milk-fed group, all nutrition was derived from the milk or milk replacer and no additional feed was offered (either starter grain or hay).…”
Section: Methodsmentioning
confidence: 99%